Reverse genetics of RNA viruses : applications and perspectives - Bridgen, Anne, 1961- (Chichester, West Sussex, UK ; Hoboken, NJ : Wiley - Blackwell, 2012)
Reverse genetics, the genetic manipulation of RNA viruses to create a wild-type or modified virus, has led to important advances in our understanding of viral gene function and interaction with host cells. Since many severe viral human and animal pathogens are RNA viruses, including those responsible for polio, measles, rotaviral diarrhoea and influenza infections, it is also an extremely powerful technique with important potential application for the prevention and control of a range of human and animal viral diseases. Reverse Genetics of RNA Viruses provides a comprehensive.
Definitions of reverse genetics, +ve, -ve, sense and doubled stranded (DS) RNA viruses / Anne Bridgen -- Coronavirus reverse genetics / Paul Britton -- Hepatitis C and use of reverse genetics in drug design / Natalia Frias Staheli -- Norovirus reverse genetics / Ian Goodfellow -- Rhabdovirus reverse genetics / Klaus Conzelmann -- Modification of measles virus and application to pathogenesis studies / Paul Duprex -- Bunyavirus reverse genetics and application to interaction with host cells / Richard Elliott -- Influenza A virus vaccines / Wendy Barclay -- Bluetongue virus reverse genetics / Mark Boyce -- Reovirus reverse genetics / Rob Hoeben -- Reverse genetics and quasispecies / Marco Vignuzzi -- Summary and perspectives / Anne Bridgen.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: RNA viruses -- Genetic aspects; Reverse genetics; RNA Viruses -- genetics; Reverse Genetics -- methods; RNA, Viral -- genetics; Viral Proteins -- genetics; Viral Vaccines; SCIENCE -- Life Sciences -- Biology; SCIENCE -- Life Sciences -- Microbiology; Electronic books